Developing Molecular Markers Linked to Corky Ringspot Resistance in Solanum tuberosum - Hu, S.; Graebner, R.; Quick, R.; Anglin, Noelle L.; Grimm, K.S.; Hofferbert, H.; Sathuvalli, V. (2025)
Corky ringspot (CRS) disease is responsible for lot rejection due to internal necrotic lesions in potato tubers. It is caused by tobacco rattle virus (TRV) which is vectored to potato by stubby root nematodes of the Paratrichodorus and Trichodorus species. Castle Russet potato variety has shown immunity to TRV and was used in two segregating biparental mapping populations to identify genomic regions linked to CRS resistance. Using 48 clones from the family POR15V001 (Castle Russet x POR08BD1-3), a single marker association analysis for CRS identified a major peak on chromosome 9. Based on the significant association with resistance, primer pairs were developed to target single nucleotide polymorphisms (SNPs, n = 22), simple sequence repeats (SSRs, n = 36), short insertions/deletions (InDels) 1 to 50 bp in length (n = 72), and long InDels larger than 50 bp in length (n = 36) using the sequence data upstream and downstream of SNP marker PotVar0108448 on chromosome 9. In total, 48 seedlings from family POR15V001 and an additional 170 seedlings from family POR16V001 (Castle Russet x A06084-2TE) were screened using each primer pair to identify markers linked to CRS resistance. Seven markers were linked to CRS resistance from Castle Russet. Four of these markers, CRINDEL20, CRINDEL490-7, CRINDEL490-6, and CRINDEL490-15, were identified as robust markers that amplify in diverse CRS-resistant germplasm, enabling their use in marker-assisted selection (MAS).